Genomic landscape of circulating tumour DNA in metastatic extramammary Paget's disease. Issue 3 (27th October 2021) - Sawamura, Soichiro; Mijiddorj Myangat, Tselmeg; Kajihara, Ikko; Tanaka, Kenichiro; Ide, Maho; Sakamoto, Ryoko; Otsuka‐Maeda, Saki; Kanemaru, Hisashi; Nishimura, Yuki; Kanazawa‐Yamada, Saori; Kashiwada‐Nakamura, Kayo; Honda, Noritoshi; et al.
Abstract: Although cancer personalized profiling by deep sequencing (CAPP‐Seq) of cell‐free DNA (cfDNA) has gained attention, the clinical utility of circulating tumour DNA (ctDNA) in extramammary Paget's disease (EMPD) has not been investigated. In this study, genomic alterations in the cfDNA and tumour tissue DNA were investigated in seven patients with metastatic EMPD. CAPP‐Seq revealed mutations in 18 genes, 11 of which have not yet been reported in EMPD. The variant allele frequency of some of the mutated genes reflected the disease course in patients with EMPD. In one patient, the mutation was detected even though imaging findings revealed no metastasis. In another patient with triple EMPD (genital area and both axilla), cfDNA sequencing detected the mutation in a rib metastatic lesion, which was also detected in both axilla lesions but not the genital region. Investigations of the ctDNA may be useful towards the elucidation of clonal evolution in EMPD.